PENGARUH GREEN MARKETING DAN ENVIRONMENTAL AWARENESS TERHADAP BRAND LOYALTY KONSUMEN SHOPPING GOODS DUA MEREK KOSMETIK TERKENAL YANG DIMEDIASI OLEH BRAND IMAGE DI SOLO RAYA - Salsabila, Shafiyah; Nasir, Moechammad (JURNAL LENTERA BISNIS, 2026)
The present research investigates how green marketing practices and environmental awareness shape consumer brand loyalty toward N’PURE and Mineral Botanica cosmetic products in the Solo Raya region. Employing an explanatory design within a quantitative framework, the study collected primary data through online questionnaires administered to 280 users of both brands. A purposive sampling technique was applied to ensure that the selected respondents met criteria aligned with the study’s objectives. Data were analyzed using Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach. The analytical procedure comprised two stages: evaluation of the outer model to assess the validity and reliability of the measurement indicators, followed by evaluation of the inner model to determine the structural relationships among the variables. The findings reveal that both green marketing and environmental awareness exert positive and significant influences on brand image and, subsequently, on brand loyalty. Furthermore, brand image functions as a mediating variable in the relationship between green marketing, environmental awareness, and loyalty. These results offer meaningful insights into how environmentally oriented marketing strategies and heightened ecological awareness can reinforce cosmetic brand loyalty through the strengthening of brand image.